The Effect of Periwinkle Flower Extract Gel (Catharanthus roseus) on MITF and GPx in C57BL/6 Mice Exposed to Sub-chronic UVB - Lidya Wulandari; Hadi Sarosa; Joko Wahyu Wibowo (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2026)
Ultraviolet B (UVB) exposure induces oxidative stress, which decreases antioxidant enzyme activity such as Glutathione Peroxidase (GPx) and activates the transcription factor Microphthalmia-associated Transcription Factor (MITF), a key regulator of melanocyte survival and melanogenic adaptation. Natural antioxidants such as Catharanthus roseus (Madagascar periwinkle) extract possess the potential to enhance endogenous antioxidant defences and modulate UVB-induced melanocyte responses. This study tries to determine the effect of Catharanthus roseus flower extract gel on MITF expression and GPx levels in the skin tissue and GPx levels in the serum of C57BL/6 mice exposed to subchronic UVB radiation. This experimental study employed a post-test only control group design with five groups: K1 (normal), K2 (negative control, gel base), K3 (positive control, vitamin E), K4 (Catharanthus roseus Extract gel 15%), and K5 (Catharanthus roseus Extract gel 30%). The mean GPx levels differed significantly (p=0.001): K1=10.66±0.85 ng/mL, K2=2.60±1.22 ng/mL, K3=3.70±1.00 ng/mL, K4=8.29±1.95 ng/mL, and K5=9.15±0.91 ng/mL. MITF expression also showed significant differences (p=0.003): K1=27.47±3.62%, K2=31.82±8.11%, K3=51.06±8.16%, K4=34.49±7.91%, and K5=40.49±3.74%. Based on these observations, it can be inferred that the administration of Catharanthus roseus flower extract gel significantly increased GPx levels and modulated MITF expression in UVB-exposed mouse skin. The 30% concentration demonstrated the most optimal antioxidant and protective effects, approaching physiological antioxidant levels, while maintaining controlled MITF activation, highlighting its potential as a natural photoprotective and antioxidant agent.